2005
DOI: 10.1029/2005jd006046
|View full text |Cite
|
Sign up to set email alerts
|

Absorption amplification of black carbon internally mixed with secondary organic aerosol

Abstract: [1] The scattering and absorption properties of black carbon (BC) particles internally mixed with secondary organic aerosol (SOA) were investigated experimentally at the large aerosol chamber facility AIDA. Diesel soot particles were coated with secondary organic compounds produced by the in situ ozonolysis of a-pinene. It was found that the organic coating strongly affects the optical and microphysical properties of the soot aggregates. Amplification factors of the internally mixed BC of 1.8 to 2.1 compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
391
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(438 citation statements)
references
References 30 publications
35
391
3
2
Order By: Relevance
“…5). These absorption coefficient amplification factors are comparable with previous laboratory and in-situ observational studies, which suggests a range of absorption enhancements from 1.05 to 3.50 due to BC mixing morphology (Bond et al, 2013;Shiraiwa et al, 2010;Schnaiter, 2005;Peng et al, 2016). Accordingly, shortwave heating rate also increased from about 0.15 K h -1 to over 0.22 K h -1 , which considerably accelerates 15 the warming effect induced by BC (Fig.…”
Section: Amplified Dome Effect By Mixing With Scattering Aerosolssupporting
confidence: 78%
“…5). These absorption coefficient amplification factors are comparable with previous laboratory and in-situ observational studies, which suggests a range of absorption enhancements from 1.05 to 3.50 due to BC mixing morphology (Bond et al, 2013;Shiraiwa et al, 2010;Schnaiter, 2005;Peng et al, 2016). Accordingly, shortwave heating rate also increased from about 0.15 K h -1 to over 0.22 K h -1 , which considerably accelerates 15 the warming effect induced by BC (Fig.…”
Section: Amplified Dome Effect By Mixing With Scattering Aerosolssupporting
confidence: 78%
“…Theoretically, condensation reduces the diameter spread between big particles and small particles over time (Seinfeld and Pandis, 2016), on the contrary to the assumption by Lack and Cappa (2010). Schnaiter et al (2005) coated BC particles with secondary organic aerosol material in a lab, and found that the coating increases particle sizes, while reduces geometric standard deviation (see 20 Fig. 5 of their paper), as predicted by theoretical calculation of condensation process.…”
mentioning
confidence: 82%
“…To obtain a realistic relationship between core size and coating thickness, we choose to use the experiment results by Schnaiter et al (2005). They coated diesel soot particles by secondary organic compounds in a chamber, and Figure realistic one in present study to compute the AAE of Coated BC, and so further coating is not addressed here.…”
Section: Bc Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification factors of MAE can reach to 1.8-2.1 when EC particles internally mixed with secondary organic aerosol (SOA) (Schnaiter et al 2005). However, the MAE of EC would decrease significantly when the size of the particle exceeds 150 nm (Bond and Bergstrom 2006).…”
Section: Impact Of Chemical Compositions On Mae Of Ecmentioning
confidence: 99%